Towards a better quality of educational peruvian management in the 21st century - Gómez Gallardo, Luz (2014)
This article aims to present the appropriate changes required by the Peruvian Educational Management, which means: have a project that is required to achieve, you select people who are considered able to do it (executives, teachers, and administrators) , which are programmed and executed actions and concrete Irlo to solve problems that impede this. Finally, educational management seeks to respond to the satisfaction of real needs and be a driver of internal dynamism of the educational units, because the most important capital is constituted by the actions of key education actors to multiply the efforts taking into account relevant aspects influence the daily practices, experiences, recognition of context and issues to those faced in pursuit of national progress and welfare.